Analisis Kadar N-total Tanah pada Pertumbuhan Tanaman Jagung yang Diberikan Pupuk NPK-Biochar-Kitosan - Roslina Imran; Astin Lukum; Wiwin Rewini Kunusa; Yuszda K. Salimi; Erni Mohamad; Arviani Arviani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Corn (Zea mays) is a widely cultivated crop in Gorontalo and has high economic value as well as an important role in food security. Fertilization is one of the key factors that influence the productivity of corn plants. This research aims to determine the combination of NPK fertilizer doses granulated with Biochar-Chitosan in enhancing the growth and productivity of corn plants, as well as its impact on the quality of total N soil content. The study was conducted by planting corn, applying fertilizer, and observing its growth through measurements of plant height, leaf length, stem diameter, cob weight with husk, and cob weight without husk. The observational data were then analyzed descriptively, summarizing or classifying the data set to provide an overview of the data. Additionally, the analysis of soil N-total content was conducted before and after the application of fertilizers. The research results show that the combination of NPK-Biochar fertilizer doses has a significant impact on the growth and productivity of corn plants. The 7.5-gram NPK-Biochar fertilizer dose yielded the best results in increasing plant height, number of leaves, stem diameter, and cob weight with and without husks compared to other doses. Soil chemical property analysis also indicates that the application of NPK-Biochar fertilizer has a positive impact on the quality of the soil's total nitrogen content.